Answer:
The larger number is 0 (zero)
Step-by-step explanation:
We start off by representing the unknown numbers with variables
Let the larger number be x while the smaller one is y
The sum of the two numbers is -9
![x\text{ + y = -9}](https://img.qammunity.org/2023/formulas/mathematics/college/nal36xqfxyfv5owlwxqd5jgvm5hkg91csq.png)
The smaller number is 9 less than the larger number:
![\begin{gathered} x-y\text{ = 9} \\ x\text{ = 9 + y} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wz3bjnf68798ly1ymek77qpyt77ons9fm1.png)
Now, insert the second equation into the first
Mathematically, we have this as:
![\begin{gathered} 9\text{ + y + y= -9} \\ 2y\text{ = -9-9} \\ 2y\text{ = -18} \\ y\text{ = }(-18)/(2) \\ y\text{ = -9} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/f875l9vamqb6o5yzex4pm10l5m59xh06sz.png)
Recall:
![\begin{gathered} x\text{ = 9 + y} \\ \text{ = 9 + (-9) = 0} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g6j3l97c7zjxv30dxwv00ly204o72uczk7.png)
0 is greater than -9 and thus, it is the larger number